1999
DOI: 10.1177/074193259902000505
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perspectives on the Collaborative Teaching Model

Abstract: Collaborative teaching, or co-teaching, is a service delivery option frequently being selected to support students with learning disabilities (LD) in general education classrooms. Despite a wealth of literature on collaborative teaching, little empirical data exist about this model. Moreover, little is known about the consumers of collaborative classes, that is, students and their parents. This article reports the findings of research employing focus groups to study the perspectives of students with and withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 11 publications
0
18
0
2
Order By: Relevance
“…Focus groups, such as those used by Copeland et al (2004) or Gerber and Popp (1999), present another alternative for understanding individuals' perceptions of social validity. Focus groups can be particularly useful when studying social validity because they (a) document individuals' shared experiences, (b) capture multiple perspectives, and (c) may make students more comfortable than individual interviews (Brotherson & Goldstein, 1992;Eder & Fingerson, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focus groups, such as those used by Copeland et al (2004) or Gerber and Popp (1999), present another alternative for understanding individuals' perceptions of social validity. Focus groups can be particularly useful when studying social validity because they (a) document individuals' shared experiences, (b) capture multiple perspectives, and (c) may make students more comfortable than individual interviews (Brotherson & Goldstein, 1992;Eder & Fingerson, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The extant literature includes some examples of researchers who used qualitative designs to conduct in-depth investigations of social validity. For example, in one study, researchers ascertained consumers' (i.e., students and parents) perspectives on the co-teaching service delivery model to support students with disabilities in the general education classroom (Gerber & Popp, 1999). The researchers conducted focus groups with 123 students and their parents across elementary, middle, and high schools in Virginia.…”
Section: A Framework For Social Validitymentioning
confidence: 99%
“…A final issue related to social validity was that only surveys and questionnaires typically involving Likert-type scales were used and, consequently, may limit the amount and type of information they offer (Leko, 2014). Several researchers have expanded on the social validity construct by using qualitative approaches in intervention research such as interviews (e.g., Broer, Doyle, & Giangreco, 2005;Copeland et al, 2004;Gerber & Popp, 1999;Leko, 2014;Lyst, Gabriel, O'Shaughnessy, Meyers, & Meyers, 2005). In the present meta-analysis 16 studies had both researchers and teachers jointly developed and conducted the FBA and subsequent interventions.…”
Section: Social Validitymentioning
confidence: 99%
“…Other common measures are other qualitative tools such as interviews or focus groups, often in combination with observations or surveys (e.g., Boudah, Schumacher, & Deshler, 1997;BruscaVega et al, 2011;Casale-Giannola, 2012;Dieker, 2001;Embury & Dinnesen, 2012;Embury & Kroeger, 2012;Gerber & Popp, 1999;Keefe & Moore, 2004;Kellems, 2014;King-Sears et al, 2014;Moin et al, 2009;Weiss & Lloyd, 2002). One researcher combined teacher interviews with student drawings of their co-teachers (Bessette, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…They said it helped them be more organized, improved their grades, and allowed them to get help more quickly. The only negatives reported were that it could be confusing when teachers disagreed with each other and that they could not get away with things because someone was always watching (Gerber & Popp, 1999;King-Sears et al, 2014;Moin et al, 2009;Scruggs et al, 2007;Wilson & Michaels, 2006). One study found contradictory information from SWDs, who said they did not receive individualized instruction in co-taught classrooms and valued at least having some access to small group or one-on-one instruction (Leadfstedt, Richards, LaMonte, & Cassidy, 2007).…”
Section: Methodsmentioning
confidence: 99%